Impact of CYP3A5, POR, and CYP2C19 Polymorphisms on Trough Concentration to Dose Ratio of Tacrolimus in Allogeneic Hematopoietic Stem Cell Transplantation - Kimitaka Suetsugu (International Journal of Molecular Sciences, 2019)
Single nucleotide polymorphisms in drug-metabolizing genes may affect tacrolimus pharmacokinetics. Here, we investigated the influence of genotypes of CYP3A5, CYP2C19, and POR on the concentration/dose (C/D) ratio of tacrolimus and episodes of acute graft-versus-host disease (GVHD) in Japanese recipients of allogeneic hematopoietic stem cell transplantation (HSCT). Thirty-six patients receiving the first HSCT using tacrolimus-based GVHD prophylaxis were enrolled with written informed consent. During continuous intravenous infusion, HSCT recipients carrying the CYP3A5*1 allele, particularly those with at least one POR*28 allele, had a significantly lower tacrolimus C/D ratio throughout all three post-HSCT weeks compared to that in recipients with POR*1/*1 (p < 0.05). The CYP3A5*3/*3 genotype and the concomitant use of voriconazole were independent predictors of an increased tacrolimus C/D ratio during the switch from continuous intravenous infusion to oral administration (p < 0.05). In recipients receiving concomitant administration of voriconazole, our results suggest an impact of not only CYP3A5 and CYP2C19 genotypes, but also plasma voriconazole concentration. Although switching from intravenous to oral administration at a ratio of 1:5 was seemingly appropriate in recipients with CYP3A5*1, a lower conversion ratio (1:2–3) was appropriate in recipients with CYP3A5*3/*3. Our results suggest that CYP3A5, POR, and CYP2C19 polymorphisms are useful biomarkers for individualized dosage adjustment of tacrolimus in HSCT recipients.